The mechanosensitive Piezo1 channel: a three‐bladed propeller‐like structure and a lever‐like mechanogating mechanism. (14th December 2018) - Zhao, Qiancheng; Zhou, Heng; Li, Xueming; Xiao, Bailong
Abstract : The evolutionarily conserved Piezo proteins, including Piezo1 and Piezo2, constitute a bona fide class of mechanosensitive (MS) cation channels, which play critical roles in various mammalian physiologies, including sensation of touch, proprioception and regulation of vascular development, and blood pressure. Furthermore, mutations in Piezos have been linked to various human genetic diseases, validating their potential as therapeutic targets. Thus, it is pivotal to understand how Piezo channels effectively convert mechanical force into selective cation permeation, and therefore precisely control the various mechanotransduction processes. On the basis of our recently determined cryoelectron microscopy structures of the full‐length 2547‐residue mouse Piezo1, structure‐guided mutagenesis, and electrophysiological and pharmacological characterizations, here we focus on reviewing the key structural features and functional components that enable Piezo1 to employ a lever‐like mechanogating mechanism to function as a sophisticated mechanotransduction channel. Abstract : The mechanosensitive Piezo1 channel possesses a 38‐TM topology model and forms a unique three‐bladed, propeller‐like structure comprising three structural and functional modules: the TM‐blade‐constituted mechanosensing module that consists of nine repetitive transmembrane helical units (THUs), the C‐terminal ion‐conducting pore module, and the transduction module including the beam, anchor, and CTD. The THU‐beam‐structure constitutes a lever‐like transduction pathway for long‐distance chemical‐ and mechanical gating of Piezo1.